Optical and Electrical Properties of Copper Telluride Thin Films - Ikhioya I. L. (International Journal of Research in Chemistry and Environment (IJRCE), 2015)
Copper Telluride (CuTe) thin films have been successfully deposited on a glass substrate Fluorine Tin oxide (FTO) by electrodeposition technique. The absorbance was measured using M501 UV-visible spectrophotometer in the wavelength range of 200-900nm. Copper Telluride (CuTe) thin films were investigated at room temperature. Optical absorption study showed that CuTe films were of indirect band gap type semiconductor with band gap energy of 2.4-2.8eV.